69‐3: Examination of Degradation Analysis of p‐i‐n Type OLEDs Devices. Issue 1 (25th September 2020) - Shirakura, Daichi; Okamura, Shinji; Taguchi, Yoshihiko; Takano, Hikaru; Shibamori, Takahiro; Miyamoto, Takashi; Sameshima, Junichiro
Abstract : Degradation analysis was conducted to p‐i‐n type OLED devices. PL, LDI‐MS, and GCIB‐TOF‐SIMS revealed the degraded layer was EML and molecular formula of the degradation product. GCIB‐TOF‐SIMS clarified the change of n‐dopant with the degradation.